On the Ways of the Dialogue of the Catholic Church with Jews and Judaism - Waldemar Chrostowski (Nicolaus Copernicus University in Toruń, 2010)
The author, Professor Waldemar Chrostowski, the former member of Polish Bishops Commission for the Dialogue with Judaism (1988-2006), presents the main points, valid both on theological and pastoral level, consisting somewhat like "Decalogue of the Catholic-Jewish Dialogue": 1. The common roots and common spiritual heritage; 2. The formula of "(in a certain way) our elder brothers"; 3. The firmness of Israel's election; 4. "Who meets Jesus Christ, meets Judaism"; 5. The responsibility (both historical and theological) for the death of Jesus; 6. Christian theology of Judaism and Jewish theology of Christianity; 7. Shoah/Holocaust and antisemitism; 8. The State of Israel, the Holy Land and Jerusalem; 9. The nature and aims of the Catholic-Jewish dialogue; 10. The possibility of cooperation and common tasks in contemporary world. The concrete solutions and inspirations given by John Paul II and Benedict XVI are mentioned.